Une enfant infirme motrice cérébrale privée de parole en apprentissage du langage écrit: évaluation et traitement - Favre, Typhelle (My University, 2003)
This article is the conclusion of our diploma study about a 12-years old girl with cerebral palsy and no functional speech. This young girl Anna is following a speech therapy in order to improve her communication, especially written language. We have given her various activities which allowed her to work her phonological sensibility. Indeed, we thought that improving her capacities in this domain would also help her to improve her written language. After comparing the initial evaluation and the evaluation after a period of treatment, we concluded that, in spite of the short length of this study, Anna seems to have progressed.